THE COMPARISON OF MICROSTRUCTURAL ARRANGEMENT OF NORMAL RETINAL LAYERS IN RAT AND HUMAN - Пальтов, Е.В.; Mateshuk-Vatseba, L.R.; Кривко, Ю.Я. (World of Medicine and Biology, 2015)
Microscopic study of the structural arrangement of normal retinal layers in rat was conducted and we obtained the following results. The research was conducted with 5 sexually mature male Wistar rats weighing 160g aged 4.5-7.5 months. Study materials are represented by histological slides of posterior retinal wall dyed with hematoxylin, eosin and azane by Heidenhain. Morphological identity in structural organization of retinal layers in rat and human was found on the basis of materials obtained in the study of morphological arrangement of normal retinal layers in rats. Retina belongs to multifunctional and multilevel multicellular structure containing complex extra- and intracellular bonds closely related to structures of the brain on one hand and to perception of light information from the other. Pigment epithelium (PE) of rat’s normal retina is a multifunctional cellular complex represented by cells closely linked to each other forming a continuous cellular skeleton. Bundles of intracellular fibrils closely linked to the cytoskeleton are located in areas of tight junctions of PE cells. These systems of intracellular bundles perform retaining interaction and are responsible for intercommunication of cells with each other. As a result such structural arrangement of PE cell layer affect the imbalance of pressure and concentration of proteins on opposite sides. Such structural peculiarity also enables activation of the mechanism of transcellular current on both sides of PE aimed at the balancing of homeostasis mechanisms. PE is also responsible for the production function of Bruch’s membrane that is responsible for controlling the selective process of nutrient transportation to the retina and it is also an external element being the morphological component of blood-retinal barrier and serves in prevention of macromolecular plasma proteins transportation. Photosensitive layer (PSL) of rat’s normal retina looks like fine-grained substance with clearly pronounced pattern. Photochemical processes of transformation of light energy into biochemical one occur in PSL cells. By microstructural PSL picture it’s complicated to conduct definitive and clear identification of morphological representation of the given cell layer. External limiting membrane (ELM) of rat’s normal retina does not resemble basal membrane in its structure. ELM is presented by reticular combination of fibrils that form the terminal parts of Muller’s cells and their tight junctions formed between them. This type of structure provides filtering process of macromolecular plasma proteins from subretinal space to the retinal tissue. External nuclear layer (ENL). External limiting membrane of rat’s normal retina separates ENL from subretinal lumen. Photoreceptor cell nuclei are located deep within this layer. Photoreceptor cell nuclei are heterochromic, closely packed and arranged in several rows. External plexiform (reticular) layer (ERL) of rat’s normal retina is the region where synapses are located responsible for transmission of nerve impulses from photoreceptor cells to bipolar ones. Inner nuclear layer (INL) of rat’s normal retina contains the highest number of cells. This peculiarity originates from the fact that it contains association neurons responsible for communication in the horizontal direction as well as the nuclear part of Muller’s cells and bipolar cells. Amacrine cell bodies are also located in INL and their processes are located in the inner reticular layer and act as the contact with ganglion cell dendrites. Ganglion cells are analyzers in the process of vertical transmission of nerve impulses from several bipolar cells to the ganglion ones. Inner plexiform (reticular) layer (IRL) of rat’s normal retina is formed by synapses of bipolar cells with ganglion cells. This layer visually has a multilayered structure. Ganglionic layer (GL) of rat’s normal retina is the least numerous. Instead, it is the most powerful if it comes to energy, due to the transmission over long distances of nerve impulses integrated by the great number of cells of the first and second neurons. GL contains bodies and nuclei of ganglionic cells and a small number of glial cells. Capillary vascular bed is also localized deep within this layer of cells. Nerve fiber layer (NFL) of rat’s normal retina draws our attention due to the fact that it has an uneven thickness throughout its location. This layer is the thinnest in the area of papillomacular bundle and contains the large number of fibers located at the nasal side of the optic nerve. This layer is represented by ganglion cell axons. Reaching the inside of the retina the fibers change their direction at right angle and run to the exit point of the optic nerve. This region does not contain myelin and Schwann’s sheaths, which leads to transparency. This layer also contains blood capillaries. Internal limiting membrane (ILM) of rat’s normal retina covers the nerve fiber layer. It is composed of proteoglycans (hyaluronic acid), collagen fibrils and basal membrane, plasmolemma, and Muller’s cells. This membrane is absent at the edges of the optic nerve and merges with the basal membrane of its glial cells.